SENSORI PIKEL UBIJALAR UNGU (Ipomoea batatas L.) YANG DIFERMENTASI SPONTAN PADA BERBAGAI TINGKAT KONSENTRASI GARAM - Neti Yuliana; Siti Nurdjanah (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2009)
This research was aimed to determine the sensory properties of purple sweet potato pickles which was spontaneously fermented for12 days at various salt concentrations (1%, 2%, 3%, 4%, 5% and 6%). The results showed that the increase of salt concentrations from 1% to 6% significantly increased sensory acceptability of purple sweet potato pickles. The best sensory properties were obtained from pickle with salt concentrations of 5% - 6%. The score of the color approaching 5 (somewhat like, and described as pink). The score of the texture was close to 3 (somewhat like, and described as hard). The score of the taste close to 4 (moderate, and described as salty). The score of the aroma close to 4 (moderate, and described as slightly acid to acid. The score of the overall acceptance was close to 4 (moderate). Keywords : pickles, purple sweet potato